Oxaliplatin induces immunogenic cells death and enhances therapeutic efficacy of checkpoint inhibitor in a model of murine lung carcinoma. (4th May 2019) - Sun, Fengfei; Cui, Lijuan; Li, Tingting; Chen, Silin; Song, Junmei; Li, Dezhi
Abstract: Background: Platinum compounds are commonly used for lung cancer treatment. However, the severe side effects and relatively poor prognosis limit their therapeutic effect. Therefore, developing novel platinum derivative and treatment strategy are critical for current lung cancer therapy. Methods: Flow cytometry, HMGB1 and ATP release, and immunoblotting were performed to evaluate the Oxaliplatin-induced immunogenic cell death (ICD) in two lung carcinoma cells. Vaccination approach and subcutaneous tumor models were created to analyze the tumor regression effect of Oxaliplatin. PD-L1 mRNA and protein levels were detected in LLC (Lewis lung carcinoma). Enhanced therapeutic efficacy of LLC was assessed by co-administration Oxaliplatin and aPD-L1 in murine lung tumor model. Results: Oxaliplatin induced robust ICD in LLC cells, activated dendritic cells (DCs, CD80 + CD86 + ) and enhanced cytotoxic T cells (CD8 + ) in LLC tumor tissues, which resulted in tumor regression. Co-administration of Oxaliplatin and checkpoint inhibitor, aPD-L1, could enhance the therapeutic efficacy of LLC in murine lung carcinoma. Conclusion: This study reveals Oxaliplatin can induce robust ICD in tumor tissues and suppress tumor growth by activating DCs and enhancing T-cell infiltration. Notably, the Oxaliplatin-induced ICD provides an immunogenic microenvironment, which enhances the checkpoint inhibitor therapeutic efficacy of LLC.